2016
DOI: 10.1039/c5fd00200a
|View full text |Cite
|
Sign up to set email alerts
|

The curious case of zeolite–clay/binder interactions and their consequences for catalyst preparation

Abstract: Zeolite-based catalyst bodies are commonly employed in a range of important industrial processes. Depending on the binder and shaping method chosen, vast differences in the reactivity, selectivity and stability are obtained. Here, three highly complementary micro-spectroscopic techniques were employed to study zeolite ZSM-5-binder interactions in SiO2-, Al2O3-, SiO2 : Al2O3- (2 : 1 mix) and kaolinite-bound catalyst pellets. We establish how their preparation influences the zeolite-clay/binder interactions. Usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
58
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 69 publications
(61 citation statements)
references
References 42 publications
3
58
0
Order By: Relevance
“…During this process it is assumed that the zeolite crystals themselves are homogeneous in nature, that is, only small variations in properties between the zeolite crystals in a batch exist. However, if this assumption is wrong and large variations in, for example, acid site density are present, parts of the shaped catalyst could become more active than others, resulting in undesired coke formation and thus a loss in catalyst activity and lifetime …”
Section: Figurementioning
confidence: 99%
“…During this process it is assumed that the zeolite crystals themselves are homogeneous in nature, that is, only small variations in properties between the zeolite crystals in a batch exist. However, if this assumption is wrong and large variations in, for example, acid site density are present, parts of the shaped catalyst could become more active than others, resulting in undesired coke formation and thus a loss in catalyst activity and lifetime …”
Section: Figurementioning
confidence: 99%
“…Calculated from the saturation adsorption amounts, the adsorption ratio for Z5-bo increased from 1.8 to 1.9 after regeneration, whereas the adsorption ratio for Z5-atp decreased from 1.9 to 1.7 after regeneration. It means that the initial para-selectivity increment for regenerated Z5-bo was not only due to the reduced acidity but partially due to the more restricted pore opening which might be caused by the aluminium species migration in alumina-bound ZSM-5 extrudates [21,31]. In the Z5-atp case, the extent of pore opening reduction decreased after regeneration, which indicated that the continuously decreased acidity of Z5-atp was the main reason for para-selectivity increment.…”
Section: Preprints (Wwwpreprintsorg) | Not Peer-reviewed | Postedmentioning
confidence: 82%
“…Prior studies have reported that extra-framework aluminum species catalyze the formation of coke (and methane) in methanol to olefins (MTO) conversion [17,29]. Moreover, aluminum in alumina-bound extrudates can migrate to the zeolite surface, forming additional Brønsted acid sites [21,31]. These extra Brønsted acid sites facilitate coking, resulting a higher coke formation rate.…”
Section: Catalytic Performance In Toluene Methylation Processmentioning
confidence: 99%
See 1 more Smart Citation
“…Imaging methods, some of them quite novel in catalysis research, 7,8 were also used widely in the work reported at the Faraday Discussion, and these included characterization of zeolitecontaining cracking catalysts investigated on the scale of microns. Important components of industrial catalysts for hydrocarbon cracking in the manufacture of petrol incorporate binders and amorphous components in addition to zeolite crystallites, and results presented at the Faraday Discussion demonstrate their high degrees heterogeneity-on the scale of micronsperhaps a surprising result in view of the enormous scale of application of cracking catalysts.…”
Section: Catalyst Characterization By X-ray Diffraction Spectroscopymentioning
confidence: 99%